The acute respiratory distress syndrome in catastrophic antiphospholipid syndrome: analysis of a series of 47 patients. Issue 1 (26th May 2005) - Bucciarelli, S; Espinosa, G; Asherson, R A; Cervera, R; Claver, G; Gómez-Puerta, J A; Ramos-Casals, M; Ingelmo, M
Abstract : Background: The acute respiratory distress syndrome (ARDS) is a non-cardiogenic form of pulmonary oedema characterised by severe hypoxaemia refractory to oxygen therapy, with diffuse pulmonary infiltrates on chest radiographs. It can be precipitated by various serious medical and surgical conditions, including systemic autoimmune diseases. The "catastrophic" variant of the antiphospholipid syndrome (APS) is an accelerated form of this systemic autoimmune condition which results in multiorgan failure because of multiple small vessel occlusions. Objective: To analyse the clinical and laboratory characteristics of patients with catastrophic APS who develop ARDS. Methods: Cases with ARDS were selected from the web site based international registry of patients with catastrophic APS (CAPS registry) (http://www.med.ub.es/MIMMUN/FORUM/CAPS.HTM ) and their characteristics examined. Results: Pulmonary involvement was reported in 150 of 220 patients with catastrophic APS (68%) and 47 patients (21%) were diagnosed as having ARDS. Nineteen (40%) of these patients died. Pathological studies were undertaken in 10 patients and thrombotic microangiopathy was present in seven. There were no differences in age, sex, precipitating factors, clinical manifestations, or mortality between catastrophic APS patients with and without ARDS. Conclusions: ARDS is the dominant pulmonary manifestation of catastrophic APS. Thus the existence of ARDS in the context of an APS makes it necessary to rule out the presence of the catastrophic variant of this syndrome.